Estudo de associação ampla do genoma bovino para lactação ajustada em 305 dias em girolando - Cruz, Alex Silva da (2015)
Genomic selection in a dairy cattle breeding is a new strategy in national livestock. Genome wide association study (GWAS) is known as a strategy that involve the use of molecular markers panels distributed throughout the genome which are selected for the identification of chromosomal regions that are important for the interest traits. The aim of this study was apply the GWAS strategy for 305-day milk yield in Girolando cows. We did the genotype from 404 Girolando and after quality control analysis remained 337 individuals and 45.622 markers. The GWAS analysis resulted in 52 SNPs associated to 305-day milk yield. Of these, 23 SNPs were linked to Known genes and only 3 SNPs were linked to NUB1, SLC24A2 and DGAT1 genes that already were associated with cattle lactation. The other SNPs have no relationships described in the cattle lactation literature. In addition, the milk production QTL analysis resulted in 52 SNPs and 14 genes linked or close to 1Mb of the SNP marker. The ARS-BFGL-NGS-414 SNP on BTA19 at 47.9Mbp is located near to GH1 gene. This gene is commonly accepted as causal gene for Quantitative Character Locus of milk production mainly affecting the yield in liters and solid milk components. Thus, our data suggest that NUB1 and SLC24A2 genes could be considered as candidate genes to understand the milk production in Girolando breed. Like this DGAT1 and GH1 genes are valuable predictive markers to be added to genomic selection of dairy cattle in breeding program.